Criteria for Judging the Quality of a Publication on Physicochemical Stability of Ready to Use Injectable Drugs - Hecq Jean-Daniel; Bihin Benoit; Jamart Jacques; Galanti Laurence (De Gruyter, 2017)
In hospitals, a major part of the drugs is administered via the intravenous route. When one wants to evaluate or know the stability of a drug in solution, it is necessary to know several physico-chemical parameters. Several reference works are available to help the hospital pharmacist with this research. However, reading these different sources can make you discover conflicting data. It is therefore necessary at this time to obtain the publications with contradictory results and to read them again. Seven criteria have been identified for judging the quality of a publication on physicochemical stability: full description of equipment, methods and analytical conditions of molecules studied; complete description of the procedures used to validate the analytical method; full indication of time testing and measurement bases or control; documentation on the analytical reproducibility; adequate statistical analysis; appropriate conclusions; appropriate references. In conclusion, everything in a compatibility study is important.